Fabrication electro-spun Poly(vinyl alcohol)-Melamine nonwoven membrane composite separator for high-power lithium-ion batteries - Wu, Xiao-Wei; Seenivasan, Manojkumar; Karuppiah, Chelladurai; Zhang, Bo-Rong; Shih, Jeng-Ywan; Hung, Tai-Feng; Chien, Wen-Chen; Ramaraj, Sayee Kannan; Rajan, Jose; Yang, Chun-Chen (Elsevier Ltd, 2024)
Current commercial separators used in lithium-ion batteries have inherent flaws, especially poor thermal stability, which pose substantial safety risks. This study introduces a high-safety composite membrane made from electrospun poly(vinyl alcohol)-melamine (PVAM) and polyvinylidene fluoride (PVDF) polymer solutions via a dip coating method, designed for high-voltage battery systems. The poly(vinyl alcohol) and melamine components enhance battery safety, while the PVDF coating improves lithium-ion conductivity. The dip-coated PVDF/Esp-PVAM composite separators were evaluated for electrolyte uptake, contact angle, thermal stability, porosity, electrochemical stability and ionic conductivity. Notably, our Dip 1 % PVDF@Esp-PVAM composite separator exhibited excellent wettability and a lithium-ion conductivity of approximately 7.75 × 10⁻⁴ S cm⁻ 1 at room temperature. These separators outperformed conventional PE separators in half-cells with Ni-rich NCM811 cathodes, showing exceptional cycling stability with 93.4 % capacity retention after 100 cycles at 1C/1C, as compared to 84.8 % for PE separators. Our Dip 1 % PVDF@Esp-PVAM composite separator demonstrates significant potential for enhancing the long-term durability and high-rate performance of lithium-ion batteries, making it a promising option for long-term energy storage applications.